The CREB and AP-1–Dependent Cell Communication Network Factor 1 Regulates Porcine Epidemic Diarrhea Virus-Induced Cell Apoptosis Inhibiting Virus Replication Through the p53 Pathway - Zhou, Hongchao; Zhang, Yuting; Wang, Jingjing; Yan, Yuchao; Liu, Yi; Shi, Xiaojie; Zhang, Qi; Xu, Xingang (Frontiers in Microbiology, 2022)
Porcine epidemic diarrhea virus (PEDV) infection causes severe diarrhea, dehydration, and high mortality in sick pigs, causing huge economic losses to the pig industry. However, the relationship between CCN1 and PEDV infection has not been reported. In this study, we showed that the expression of CCN1 was enhanced by PEDV infection and we observed that PEDV promotes the CREB and AP-1 activation to promote CCN1 expression. The PKA and p38 inhibitor significantly suppress CCN1 expression, indicating that PEDV-induced CCN1 expression may be through PKA and p38 pathway. Further tests determine that CREB and AP-1 were regulated respectively by PKA and p38. CCN1 overexpression decreased PEDV replication and CCN1 knockdown increased PEDV replication. We proved that CCN1 overexpression increased p53 phosphorylation levels, promoted Bax expression and the caspase 9 and caspase 3 cleaveage, inhibited Bcl-2 production. CCN1 knockdown decreased p53 phosphorylation levels, inhibited Bax production and caspase 9 and caspase 3 cleaveage, promoted Bcl-2 expression. The treatment of PFT-α (p53 inhibitor) significantly suppressed cleaved caspase 9 and caspase 3 expression, resulting in cell apoptosis decrease. Taken together, these studies showed that PEDV promotes the activation of CREB and AP-1 to increase CCN1 expression, overexpression of CCN1 promotes apoptosis by elevating p53 protein phosphorylation and inhibits PEDV replication, and knockdown of CCN1 inhibits apoptosis by decreasing p53 protein phosphorylation and promotes PEDV replication. Our study could provide some reference for the molecular mechanisms of PEDV-induced CCN1 induction and supply a new therapeutic target for PEDV.